Teacher education for an inclusive school system: Connecting policy and classroom practice - Óskarsdóttir, Edda; Emilsson Peskova, Renata (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This article examines how pre-service teachers are prepared to teach linguistically and culturally diverse learners. Document analysis examined the current policy framework in Iceland and provided an insight into how the policy is guiding praxis in teacher education. The findings reveal contrasting ideologies in education policies and measures in Iceland, as well as a missing link from theory to didactics in teacher education regarding teaching in diverse classrooms. To ensure equity in education, developing teacher knowledge and perspectives about diversity is crucial, as well as providing teachers with solid pedagogical tools. These enable them to practice inclusive pedagogy in multicultural and multilingual school environments where neoliberal and neoconservative voices have gained influence.